2023
DOI: 10.1242/dmm.050200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the FUS nuclear localisation signal domain causes neurodevelopmental and systemic metabolic alterations

Zeinab Ali,
Juan M. Godoy-Corchuelo,
Aurea B. Martins-Bach
et al.

Abstract: Mutations in the ubiquitously expressed DNA/RNA binding protein FUS cause aggressive juvenile forms of amyotrophic lateral sclerosis (ALS). While most FUS mutation studies have focused on motor neuron degeneration, little is known about wider systemic or developmental effects. We studied pleiotropic phenotypes in a physiological knock-in mouse model carrying the pathogenic FUSDelta14 mutation in homozygosity. RNA sequencing of multiple organs aimed to identify pathways altered by the mutant protein in the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…This is in accordance with a previous finding from TDP-43 Q331K KI mice, although the abnormalities found here in M323K mutant mice are more severe (Lin et al, 2021). Overall, this suggests an essential role for TDP-43 in the correct development and maintenance of the central nervous system, as in the case for other hnRNP family proteins, such as FUS (Ali et al, 2023). Interestingly, MRI analysis of mutant TARDBP ALS patients have shown that TDP-43 mutations can lead to distinct cortical alterations as well as white matter abnormalities (Spinelli et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with a previous finding from TDP-43 Q331K KI mice, although the abnormalities found here in M323K mutant mice are more severe (Lin et al, 2021). Overall, this suggests an essential role for TDP-43 in the correct development and maintenance of the central nervous system, as in the case for other hnRNP family proteins, such as FUS (Ali et al, 2023). Interestingly, MRI analysis of mutant TARDBP ALS patients have shown that TDP-43 mutations can lead to distinct cortical alterations as well as white matter abnormalities (Spinelli et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with a previous finding from TDP-43 Q331K KI mice, although the abnormalities found here in M323K mutant mice are more severe ( Lin et al, 2021 ). Overall, this suggests an essential role for TDP-43 in the correct development and maintenance of the CNS, as in the case for other hnRNP family proteins, such as FUS ( Ali et al, 2023 ). Interestingly, MRI analysis of mutant TARDBP ALS patients have shown that TDP-43 mutations can lead to distinct cortical alterations as well as white matter abnormalities ( Spinelli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 83%